Expressing the gene encoding 34-kilodalton outer membrane protein of Brucella melitensis for development of a recombinant vaccine - Yulianna Puspitasari, . (2011)
Brucella is a Gram-negative, facultative intracellular bacterium that causes severe disease in both humans and animals. Brucellosis is still endemic in many developing countries, impairing animal health and productivity leading to important economic losses. Brucella melitensis causes abortions in sheep, goats, and cattle, and it is considered the most pathogenic Brucella spp. in humans. Currently, vaccination has been accepted as the best mean of control for brucellosis in small ruminant, with the aim at decreasing the prevalence of the disease to an acceptable level. Among available vaccines, Brucella melitensis Rev. 1, an attenuated smooth strain used to control Brucella melitensis infection in small ruminants, gives heterologous protection against Brucella ovis and is currently considered the best vaccine for the prophylaxis of brucellosis in sheep and goats. Yet Rev 1 has several disadvantages, namely residual virulence able to induce abortion in pregnant animals; a capacity to elicit antibodies against smooth lipopolysaccharide (S-LPS) which interferes in the differential diagnosis between vaccinated and naturally infected animals; it is resistant to streptomycin, one of the antibiotics of choice used to treat brucellosis; it is pathogenic for humans; and its use is prohibited in countries free of Brucella melitensis. These several drawbacks indicate the need for a better vaccine for brucellosis eradication. This study was conducted to analyze the outer membrane protein (Omp) profile and determine the antigenicity of local isolates of Brucella melitensis, followed by development of recombinant cells expressing the selected Omp and finally, study the immune response following exposure to the recombinant cells. The Omps of local isolates of Brucella melitensis strains 152, 183, and 293 were extracted using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) producing three major and four minor Omp bands, which were common in all isolates. They were the 25, 34 and 89 kDa major bands and the 16, 30, 43 and 70 kDa minor bands. Subsequent immunobloting identified consistently common antigenic bands that were shared by all strains. They were the 16, 34 and 70 kDa bands. The 34 kDa was the only major Omp band found to be antigenic. Investigations at the molecular level involved isolation and detection of the gene encoding 34 kDa Omp of Brucella melitensis strain 293. As a result from the cloning procedures, the recombinant vectors, pET32/LIC-Omp34 plasmid was created. Sequencing analysis showed that the gene of interest was authentic and kept in frame with the vector sequence. It was confirmed that the inserted gene as the Omp 34 kDa gene of Brucella melitensis strain 293 and was found to contain 927 bp. The gene encodes a deduced protein of 309 amino acids. Analysis of the nucleotide sequence of Omp 34 kDa gene of Brucella melitensis strain 293 revealed 100% homology to the porin of Brucella melitensis bv. 1 strain 16M and 99% to 98% homology to the Brucella melitensis porin (Omp2a) and (Omp2b) genes. In developing the recombinant cell expressing the Omp 34 kDa, SDS-PAGE and Western immunoblotting analyses revealed that the expressed fusion protein of the pET32/LIC-Omp34 was approximately 51 kDa, which contained 17 kDa of tagged protein and remaining is 34 kDa of the Omp. The results conclusively demonstrated the successful expression of Brucella melitensis Omp 34 kDa gene as a fusion protein, which was tested in an Escherichia coli strain. The next experiment involved in vivo efficacy of the recombinant Escherichia coli cells in stimulating humoral and cell-mediated immune responses in goats. During the course of study, both serum and blood from all groups; vaccinated and unvaccinated were collected to evaluate the antibody levels via enzyme-linked immunosorbent assay (ELISA) and cell mediated immunity response of CD4+ and CD8+ T cells via immunofluorescent assay. Overall, it was found that goats immunized with recombinant cell or whole-cell followed by a booster dose on day 14, showed strong specific and significantly higher (p<0.05) IgG response when compared to the unvaccinated group throughout the entire 8-week study period. Significantly (p<0.05) high antibody levels was observed as early as week 1 post-vaccination and the titers was considerably increased after boosting. In contrast, the systemic cellular immune response, particularly the CD4+ and CD8+ T cells did not increase after the first and second exposures to the recombinant cells, but significant (p<0.05) responses cells were observed only at weeks 4 and 5. This was much inferior than the response following exposures to whole-cell that resulted in significant (p<0.05) increased as early as week 1 post-exposure. These results demonstrated that despite the high antibody level of IgG responses, vaccination with the recombinant Escherichia coli cells expressing the OMP34 kDa gene of Brucella melitensis strain 293 was capable of eliciting delayed systemic CD4+ and CD8+ T cells responses that lasted for a short period of time. This study revealed that the Omp 34 kDa of Brucella melitensis strain 293 was immunogenic. Following preparation of recombinant cells expressing the gene encoding 34 kDa Omp, exposures to goats were capable to elicit high antibody levels. However, the systemic CD4+ and CD8+ T cells responses was delayed and lasted for a short period of time. Thus, further study is needed with the intention of boosting the cell-mediated immune responses.